The role of MRI in the management of a prostate cancer patient with bone and lymph nodes metastases. A case report. - Belmonte, Maddalena; Saia, Giulia; Zugni, Fabio; Alessi, Sarah; Colombo, Alberto; Summers, Paul E.; Luzzago, Stefano; Marvaso, Giulia; Musi, Gennaro; De Cobelli, Ottavio; Jereczek-Fossa, Barbara A.; Petralia, Giuseppe (Acta Biomedica Atenei Parmensis, 2021)
The use of multiparametric prostate magnetic resonance imaging (mpMRI) is recommended, in the European Association of Urology (EAU) guidelines, for local staging of patients with prostate cancer (PCa). Systemic staging is recommended only for patients with unfavourable intermediate and high-risk disease; with bone and lymph node assessments usually being performed using bone scan (BS) and computed tomography (CT), respectively. Magnetic resonance imaging (MRI) is the imaging technique with the highest sensitivity for the detection of bone metastases and has shown promising results also for lymph node assessments. In this report we illustrate how MRI provided a comprehensive assessment of local disease as well as bone and lymph node metastases in a patient with PCa. (www.actabiomedica.it)